Removal of oxytetracycline by graphene oxide and Boron-doped reduced graphene oxide: A combined density function Theory, molecular dynamics simulation and experimental study - El Hadki, Ahmed; Ulucan-Altuntas, Kubra; El Hadki, Hamza; Ustundag, Cem Bulent; Kabbaj, Oum Keltoum; Dahchour, Abdelmalek; Komiha, Najia; Zrineh, Abdallah; Debik, Eyup (ELSEVIER, 2021)
Graphene-based nanomaterials have demonstrated great potential in the field of environmental applications, especially on water treatment processes. Accordingly, herein, in order to be used as adsorbent in the removal of oxytetracycline (OTC), graphene oxide (GO) and boron doped reduced graphene oxide (B-rGO) was investigated. GO was obtained through the oxidation/exfoliation process using the modified Hummers' Method and further etched by a thermal annealing approach to obtain B-rGO, utilizing boric acid as boron source for the study. FT-IR, TEM and XRD were used to characterize the morphology properties of GO and B-rGO and confirm the success of these synthesis. To evaluate the degradation potential of OTC by GO and B-rGO, pH of the sample, GO and B-rGO concentration, initial OTC concentration, reaction time and temperature has been selected as effective parameters. Based on the obtained experimental results GO and B-rGO were found to possess favorable adsorption efficiencies reaching 86% and 100% for GO and B-rGO, respectively, rapidly uptake rate with up to 85% of total removal occurring within the initial 10 min. In addition, it is noteworthy that OTC removal from solution was strongly dependent on pH but independent of temperature. The classical isotherm and kinetic adsorption models suggested that the process perfectly conformed to Freundlich and Pseudo-second-order model (R2 >= 0.95). Furthermore, density functional theory (DFT) simulation performed at the B3PW91 level of theory as well as a topological analysis were introduced to elucidate theoretically the interfacial interaction at the molecular-scale associated with OTC sorption on both adsorbents.
Keywords: Adsorption; Graphene oxide; Boron-doped reduced graphene oxide; Oxytetracycline; DFT; Topological analysis; Molecular dynamics; WASTE-WATER TREATMENT; ADSORPTION CHARACTERISTICS; AQUEOUS-SOLUTION; DEGRADATION; COMPOSITES; TETRACYCLINES; ANTIBIOTICS; PERFORMANCE; OXIDATION; SHELL; Chemistry; Materials Science